OPTIMIZATION OF LINE SIZING OF THERMAL POWER STATION - JANKAR, Mr. SUNIL; RATHORE, Prof. R S; GUPTA, Prof. ASHOK KUMAR (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
General layout and location of steam consuming equipment is of great importance in efficient distribution of steam. Steam pipes should be laid by the shortest possible distance rather than to follow a building layout or road etc. However, this may come in the way of aesthetic design and architect’s plans and a compromise may be necessary while laying new pipes. Apart from proper sizing of pipe lines, provision must be made for proper draining of condensate which is bound to form as steam travels along the pipe.